SAT0061 Concurrent Ultrasound-Detected Synovitis and Tenosynovitis Predict Flare in Patients with Rheumatoid Arthritis in Clinical Remission. (15th July 2016) - Sakellariou, G.; Bellis, E.; Scirè, C.A.; Carrara, G.; Adinolfi, A.; Bortoluzzi, A.; Batticciotto, A.; Cagnotto, G.; Caprioli, M.; Canzoni, M.; Cavatorta, F.P.; De Lucia, O.; et al.
Abstract : Background: Subclinical synovial inflammation detected by ultrasonography (US) in patients with rheumatoid arthritis (RA) in clinical remission relates to disease flare. The impact of tenosynovitis in this context is not known. Objectives: To evaluate the association between US-detected tenosynovitis and synovitis in RA patients in clinical remission and flare over 12-months. Methods: STARTER is a multicentre cohort study of the US Study Group of the Italian Society for Rheumatology. Participants were selected on the basis of a reliability exercise and the availability of high-end equipment. Patients with RA in clinical remission underwent clinical evaluation and US synovitis (-S) and tenosynovitis (-T) were assessed categorically for Grey Scale (GS) and power Doppler (PD) at 11 joints, extensor and flexor tendons in both hands and wrists. Patients were seen at 6 and 12 months. Flare within 12 months was defined as increase of >1.2 or >0.6 if final DAS28>3.2. The relationship between the presence of GS-T/-S, PD-T/-S was evaluated by logistic models, presented as odds ratios (OR) and 95% confidence interval (CI), adjusted for pre-specified confounders. Results: 361 patients (72.3% f, mean age (sd) 56.1 (13.3), median disease duration (IQR) 7.1 years (3.6–13.5)) were included. 98/326 (30.6%) patients had a flare within 12 months. Considering US variables separately, only PD-S significantly predicted flare (OR 1.87 (1.12, 3.14)). When the model included both –T and –S, only the concurrent presence of –T and –S predicted flare (PD-T+-S: OR 2.06 (1.04, 4.07); GS-T+-S: OR 2.27, (1.01, 5.10)), while isolated –S and –T did not. Conclusions: In patients with RA in clinical remission, US-detected synovial and tenosynovial inflammation identifies patients at risk of flare. US might help decisions on management in this population. Disclosure of Interest: None declared